Effects of Plasmonic Metal Core -Dielectric Shell Nanoparticles on the Broadband Light Absorption Enhancement in Thin Film Solar Cells - Peng Yu (Nature Portfolio, 2017)
Abstract To guide the design of plasmonic solar cells, theoretical investigation of core (metal)-shell (dielectric) nanoparticles for light absorption enhancement in thin film Si solar cells is performed. In contrast to the reported simulations and experimental results that rear-located surface plasmon on bare metallic nanoparticles is preferred, the core-shell nanoparticles demonstrate better performance when surface plasmon is located in front of a solar cell. This has been attributed to the enhanced forward scattering with vanishing backward scattering preserved over a wide spectral range in core-shell nanoparticles. This work provides a concept to achieve enhanced forward scattering with weakened backward scattering in plasmonic thin film solar cells.